Potensi Nilai Kalor Biomassa Dari Ampas Tebu (Bagasse) Yang Bersumber Dari Penjual Minuman Sari Tebu Di Kota Pontianak - Reza Wahyudi; Muhammad Ivanto; Murti Juliandari (Jurnal Serambi Engineering, 2021)
Dependence on the provision of electricity using fossil fuels is a major energy supply problem in Indonesia. Therefore, it is necessary to provide new and renewable alternative fuels that are effective, efficient, and environmentally friendly. One of the alternative fuels is bagasse biomass. The purpose of this study was to determine the amount of bagasse produced by sellers of sugarcane juice drink in Pontianak City, in order to determine the estimated value of bagasse. The research method used was direct data collection and laboratory testing . Based on the results of the study, the number of vendors of sugarcane juice beverages producing bagasse was 169. Of this amount, produce bagasse that can reach 1,030.9 kg/day. Based on the test results, the estimated moisture content of bagasse was 3.28%, ash content was 0.77%, and carbon remained at 7.65%. So, if converted with the test results of the calorific value of bagasse and made into briquettes bagasse (bio briquettes), which is 19,648 kJ/kg with a density of 0.416 kg/m3, then converted into a potential calorific value of 242,849,280 J/year.